KAJIAN BENTUK DAN MAKNA LINGGA DALAM PERSPEKTIF TEOLOGI HINDU (Studi Lingga Sebagai Media Pemujaan di Desa Linggoasri, Kecamatan Kajen, Kabupaten Pekalongan - Jawa Tengah) - Suhardi, Untung (Mahasiswa S2 Brahma Widya, 2013)
Based on the research I have done that from the ritualistic worship of the phallus had a form that the phallus is Linggoasri concluded that the form of the phallus is the phallus-shaped with a rectangular base (brahma Bhaga), with the length of the Valentine (swastika phallus) and the top ardhacandrakara shaped (shaped in a half circle). Furthermore, the phallus worship experience barriers ie, the notion of non-Hindu people as primitive doctrine, Hindus in the village Linggoasri tend to close themselves in the implementation of Hinduism, it is influenced by factors in that the dynamics of the population, a finding that evolving society and the internal conflict in Hindus and people of other factors of out harhass, and other cultural influences community and lack of optimal development of Hindu religious instructor. In addition the solution by way of understanding the teachings of Hindu neighbor to the younger generation, established tolerance for inter-religious Hindus themselves, increasing extension of traditional institutions and government agencies, and procurement of books based on the Hindu religion. This is done to understand the deep meaning of the phallus worship performed by the Village Linggoasri. Keywords : Worship of Linga, Philosophy, Obstacles and solution.